Financial performance evaluation and correlation of selected key financial ratio and stock price: a case study of indonesia lq45 state owned enterprises construction companies - Perdana Suherman Putra, Aditya; M. Daryanto, Wiwiek (The Indonesian Journal of Business Administration, 2018)
Abstract. Indonesia Infrastructure development budget of 2015 – 2019 reached Rp 4.197 trillion and 42 percent of it relies on the State Owned Enterprise (SOEs) income. Adhi Karya (ADHI), Jasa Marga (JSMR), PT. PP (PTPP), Wijaya Karya (WIKA) and Waskita Karya (WSKT) are five SOEs Construction Companies listed in LQ45 in July 2018 and act as a responded in this study. The objective of this study is to measure company financial health using eight ratios investigating; 1) return on equity, 2) return on investment, 3) cash ratio, 4) current ratio, 5) collection period, 6) inventory turnover, 7) total asset turnover and 8) total equity to total asset ratio based on audited financial reports of 2013 – 2017 and be validated using the decree of Ministry of SOEs No.KEP100/MBU/2002. Validation using statistical method was also been used by The Pearson Product-Moment Correlation Coefficient (PMCC) to determine the correlation of financial performance with stock price. The results show that the five SOEs were in healthy conditions, except ADHI in 2016 and JSMR in 2013 – 2015 and 2017. The rank of health level were as follow; 1) WSKT (AA, AA, A, AA, AA); 2) PTPP (AA, AA, AA, A, AA); 3) WIKA (AA, AA, AA, A, A); 4) ADHI (AA, AA, A, BBB, A) and 5) JSMR (BBB, BBB, BBB, A, BBB). PMCC shows that the Net Profit Margin has the strongest significant correlation with stock price. Keywords: financial ratios, financial health assessment, SOEs construction, stock price, PMCC.